Expert judgement elicitation for risk assessments of critical infrastructures - Cooke, R. M.; Goossens, L. H. J. (Journal of risk research, 2004)
Governmental bodies and companies are confronted with the problem of achieving rational consensus in the face of substantial uncertainties. The subject area of this special issue (risk and vulnerability assessments and management of critical infrastructures) might be a good example as are risk management of chemical installations and accident consequence management for nuclear power plants. Decisions with regard to infrastructures functioning and possible malfunctioning must be taken on the basis of predictions of technical and organizational system behaviour. These predictions use mathematical models containing scores of uncertain parameters. Decision makers want to take, and want to be perceived to take, these decisions in a rational manner. The question is, how can this be accomplished in the face of large uncertainties? One available source is experts in the many fields of interest within infrastructures. This paper describes the use of structured expert judgement in a formal manner. The paper refers to the Procedures Guide published by the European Union as EUR 18820. This Procedures Guide addresses two methods for using expert judgements developed at Delft University of Technology. The paired comparisons method is particularly suitable to identify the relative importance of attributes in the risk management arena, while the Classical Model, apt to arrive at subjective probability assessments, is particularly suitable to derive uncertainty distributions over model parameters. Examples will be referred to for further illustration of applications relevant in the field of risk assessment and risk management.